An Evaluation of the Swedish Earned Income Tax Credit - Karin Edmark; Che-Yuan Liang; Eva Mörk; Håkan Selin (Research Institute of Industrial Economics (IFN), 2012)
Over the last twenty years we have seen an increasing use of in-work tax subsidies to encourage labor supply among low-income groups. In Sweden, a non-targeted earned income tax credit was introduced in 2007, and was reinforced in 2008, 2009 and 2010. The stated motive of the reform was to boost employment; in particular to provide incentives for individuals to go from unemployment to, at least, part-time work. In this paper we try to analyze the extensive margin labor supply effects of the Swedish earned income tax credit reform up to 2008. For identification we exploit the fact that the size of the tax credit, as well as the resulting average tax rate, is a function of the municipality of residence and income if working. However, throughout the analysis we find placebo effects that are similar in size to the estimated reform effects. In addition, the results are sensitive with respect to how we define employment, which is especially true when we analyze different subgroups such as men and women, married and singles. Our conclusion is that the identifying variation is too small and potentially endogenous and that it is therefore not possible to use this variation to perform a quasi-experimental evaluation of the Swedish EITC-reform.
Keywords: H24; J21; 330; Labor supply; Labor force participation; Tax incentives; Steuervergünstigung; Arbeitsangebot; Erwerbstätigkeit; Wirkungsanalyse; Schweden